(untitled) (Proceedings of the International Conference on Agriculture, 2024)
The MD2 variety of pineapple exhibits a substantial level of demand from both China and the Middle East, emphasising the significance of this crop in these regions. Most pineapple cultivation in Malaysia occurs in peat soil, requiring substantial fertiliser application throughout growth. Peat soil exhibits limited productivity and does not adequately facilitate optimal plant growth. A research investigation was undertaken to mitigate the reliance on traditional fertilisers by utilising capsular fertilisers and microbes to improve the growth of pineapple crops in peat soil. Seven treatments and four replications were performed using conventional pineapple fertiliser and capsule fertiliser with microbes at various fertiliser application rates. The pineapple cultivar employed in this study is MD2. The findings indicate no statistically significant impact on pineapple morphology when comparing capsule fertiliser and microbes to conventional fertiliser. However, the fruit weight of conventional fertiliser is slightly heavier. Nevertheless, in terms of flavour, pineapple cultivated with capsule and microbial fertiliser exhibits a more pronounced sweetness than conventional fertiliser. The observed nutrient content in the soil did not demonstrate a statistically significant impact across all treatment conditions. Nevertheless, utilising capsule fertilisers containing microbes with lower application rates than conventional fertilisers proves to be a viable approach in mitigating the overreliance on chemical fertilisers while concurrently fostering the growth of pineapple plants..